The Rhode Island Colony - Italia, Bob (Edina, Minnesota ABDO Publishing Company, 2001)
Provides a history of Rhode Island from before the arrival of European explorers in the 16th century to its statehood in 1790.
Keywords: Rhode Island - History - Colonial period, ca. 1600-1775.